Green School Project (GSP): A Case Study in Sukma Bangsa Lhokseumawe School, Aceh Indonesia - Hajar, Siti (SUKMA: Jurnal Pendidikan, 2023)
The Green School Project (GSP) is a program that was initiated based on monitoring and mutual awareness of the success of experiences in overcoming the many environmental problems that occur in schools. Starting from the discomfort of the school community because the conditions and atmosphere of the school are spacious but look rather hot and dry; rubbish scattered at almost all points in the school area, and the habit of eating unhealthy food in certain packages. However, several activities were conducted as the effective solutions when all school residents take the concrete action together consistently through GSP program. This is a study case of 163 students of the total 200 students of SMP Sukma Bangsa Lhokseumawe. The data was collected by observation, interview, and survey. This study intended to evaluate whether the GSP program has been effectively affected to improve our students awareness, carin,g and loving to the school cleanliness and health. As a result, the good habits coordinated by the GSP Team of Sukma Bangsa Lhokseumawe school are successfully build the character of students who care more about the school environment. The green, clean and healthy condition of the school today were considered as the great contribution of all school managements, teachers and parents as role models in order to achieve the targets for behavior change of the students of Sukma Bangsa Lhokseumawe School who become more loving a green, clean and healthy school environment.